Responsibility for employees as a challenge for contemporary organizations - Magdalena Wrob́el (The Central European Review of Economics and Management (CEREM), 2019)
Aim: The paper considers the issue of responsibility on the part of contemporary organizations for their employees. In her paper, the author described ISO 26000 guidelines for organizations concerning labor practices and the impact of these guidelines on competitiveness of organizations. The paper also analyzed labor practices implemented by firms in Poland in the years 2013-2015.~Design / Research methods: Based on statistical data and literature study as well as Responsible Business in Poland. Good practices reports., the period 2013-2015 is considered for analysis.~Conclusions / findings: Entrepreneurs in Poland seem to take more responsibility for employees, while recognizing the key role played by human capital in building competitive advantage of an organization. This also supports the company's image and competitiveness, while improving employee loyalty.
Keywords: O15; M14; M50; 330; human capital; contemporary organizations; responsibility for employees; corporate social responsibility; ISO 26000 standard; Poland